The Relation between Teachers’ and Children’s Playfulness: A Pilot Study - Pinchover, Shulamit (Frontiers in Psychology, 2017)
Young children spend considerable time in educational settings, in which traditionally, their primary occupation is play. A playful preschool environment has been related to better cognitive, social and emotional development. Although it is assumed that teachers’ playful behaviors are important in creating a playful school environment, empirical knowledge on this subject is lacking. The current study pilot examines the relation between teachers’ and children’s playfulness. Thirty-one teacher-child dyads participated. The teachers were asked to complete the Adult Playfulness Scale (APS). Thirty-minute videotapes of teacher-child play interactions were used to evaluate the child’s playfulness using the Test of Playfulness. A positive relation was found between two of the APS subscales (spontaneity and silliness) and child playfulness. Teacher silliness mediated the relation between children’s age and playfulness. This study is the first to show that teachers’ playfulness aspects are related to higher playfulness in children. Promoting teachers’ playful behaviors can be related to better teacher-child playful interactions, thereby enhancing children’s playfulness.